Talk with me! Parental linguistic input to toddlers with moderate hearing loss. Issue 1 (January 2020) - DIRKS, Evelien; STEVENS, Angela; KOK, Sigrid; FRIJNS, Johan; RIEFFE, Carolien
Abstract: This study examined the quantity and quality of parental linguistic input to toddlers with moderate hearing loss (MHL) compared with toddlers with normal hearing (NH). The linguistic input to eighteen toddlers with MHL and twenty-four toddlers with NH was examined during a 10-minute free-play activity in their home environment. Results showed that toddlers with MHL were exposed to an equivalent amount of parental linguistic input compared to toddlers with NH. However, parents of toddlers with MHL used less high-level facilitative language techniques, used less mental state language, and used shorter utterances than parents of toddlers with NH. Quantity and quality measures of parental linguistic input were positively related to the expressive language abilities of toddlers with MHL.